COVID-19 and the ageing immune system in an elderly patient : a case report - I Gusti Putu Suka Aryana; Ida Ayu Pradnya Paramita (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundThe severity of COVID-19 infection has an increasing trend in the elderly, which contributes to the high morbidity and mortality rates in this population. Aging itself is a prominent risk factor for severe disease and death from COVID-19. Case DescriptionThis case report a 71-year-old woman who complained of shortness of breath for 3 days before being admitted to the hospital. Bilateral consolidation and increased bronchovascular pattern were found on chest radiograph, and a positive SARS-COV2 nasopharyngeal swab PCR test result was noted. This patient was diagnosed with confirmed severe manifestation of COVID-19, community-acquired pneumonia and type 1 respiratory failure, as well as type II diabetes mellitus and suspicion of acute gastritis. The results of the geriatric status assessment were moderate functional status, risk of malnutrition, and moderate risk of deep vein thrombosis (DVT). This patient underwent treatment in accordance with the COVID-19 protocol along with management for geriatric status improvement. The patient was given permission to return home after 14 days of treatment, during which time her health had improved and her functional status had changed to moderate dependency. During follow-up, the patient continued to receive therapy. She is still being observed and future evaluations will be conducted. ConclusionThe increased susceptibility of the elderly to COVID-19 infection is caused by various factors. A burden of death and long-term disability brought on by this pandemic may be lessened by new or modified therapies that target aging-associated mechanisms. Therefore, COVID-19 case management in this population should be done with a comprehensive approach.